PENGEMBANGANLEMBAR KERJA SISWA (LKS) MATEMATIKA POKOK BAHASAN SISTEM PERSAMAAN LINIER DUA VARIABEL UNTUK SMP KELAS VIII BERDASARKAN STANDAR PROSES NCTM (NATIONAL COUNCIL OF TEACHER OF MATHEMATICS) - K, Alvian Agung; Suharto, S; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2014)
Abstract.The purposeofthis studyistodevelop aNCTMprocess standards based worksheet. Thedevelopment Researchmodelrefers toThiagarajan4-D model. It consistsoffourstages, namelydefine stage, design stage,development stage, and disseminate stage.Thereare twoproductsthis research. Theyareworksheets andfinaltestinstrument. The worksheetconsistsoffiveprocess standards, namelyproblem solving, reasoningandproof, communication, connections, andrepresentation. All productsobtainedin this research have satisfied validity, practicality and effective criteria. Their scores are respectively4.33forvalidity, 89.55% forpracticality, 88 % foreffectiveness. It can be concluded that those products can be used as mathematics learning material in a class. Keywords:4D Thiagarajan models, student worksheet, NCTM process standards, Linier Equation System in Two Variable